34.9k views
4 votes
Look at this equation. -6+(-6)+(-6)+(-6)+[(-4)+(-4)+(-4)+(-4)+(-4)+(-4)]=(-6)(x) What is the missing number that makes this equation true?

User Nomadus
by
5.7k points

2 Answers

4 votes
-6+(-6)+(-6)+(-6)+[(-4)+(-4)+(-4)+(-4)+(-4)+(-4)] = (-6)(x)

4(-6) + 6(-4) = -6x

-48 = -6x

8 = x

Final answer: 8

User RajuPedda
by
6.4k points
3 votes
There are four - 6s and six - 4s. We can simplify your equation to become this:

4(- 6) + 6(- 4) = - 6x
- 24 - 24 = - 6x
- 48 = -6x
x = 8

Your missing number is 8.
User Vencovsky
by
6.0k points